Peterson's graduate and professional programs an overview 2016 (Albany Peterson's, 2016)
Graduate & Professional Programs: An Overview 2016 contains more than 2,250 university and college profiles with detailed information on the degrees available, enrollment figures, tuition, financial support, housing, faculty, research affiliations, library facilities, and contact information. This graduate guide enables students to explore program listings by field, geographic area, and institution. Two-page in-depth descriptions, written by each featured institution, give complete details on the graduate study available. Up-to-date appendixes list institution changes since the last edition and abbreviations used in the guide. Graduate & Professional Programs: An Overview 2016 is the latest in Peterson's 50-year history of providing prospective students the most up-to-date graduate school information available.
Keywords: Universities and colleges- Graduate work; Education - study and teaching